"The founder of an independent state, a great statesman and politician" (Journal of Universal Science Research, 2023)
In this article, the founder of the independent state of Uzbekistan, a great statesman and political figure, an honored son of the Uzbek people, the First President of our country, Islam Abdugyanevich Karimov, freed our country from the dependence of the autocratic system and restored our country, which was on the brink of destruction, a brilliant political  It has been widely reported that he left an indelible mark in history by showing selflessness in the way of the welfare of the people and the development of the country with his noble human qualities.  Islam Abduganiyevich Karimov left an indelible mark in the centuries-old history of our country with his brilliant political activity and noble human qualities.  He was recognized as a great person and figure who received great respect and prestige not only in Uzbekistan, but also in the world.